2020
DOI: 10.1155/2020/8919515
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation-Guided Approach to Pulmonary Artery Catheter Ablation in Patients with Idiopathic Pulmonary Arterial Hypertension: A Pilot Feasibility Study with a 12-Month Follow-Up

Abstract: Background. Recently, transcatheter pulmonary artery (PA) ablation aiming at sympathetic denervation has been proposed in pulmonary arterial hypertension (PAH). This pilot feasibility study aimed to assess the feasibility of selective radiofrequency PA ablation based on response to high-frequency stimulation mapping. Methods. The study comprised 3 female patients with idiopathic PAH (IPAH). The following reactions to PA stimulation were noted and marked by color points on the three-dimensional map: sinus brady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…We cannot exclude the difference in the stimulation protocols between our study and previous studies. However, a very similar stimulation approach protocol was affective in provoking autonomic reactions when used in other large vessels [18]. We suggest that pain perception during RA stimulation might be Cardiovascular Therapeutics responsible for some BP elevation.…”
Section: Renal Artery Stimulationmentioning
confidence: 79%
“…We cannot exclude the difference in the stimulation protocols between our study and previous studies. However, a very similar stimulation approach protocol was affective in provoking autonomic reactions when used in other large vessels [18]. We suggest that pain perception during RA stimulation might be Cardiovascular Therapeutics responsible for some BP elevation.…”
Section: Renal Artery Stimulationmentioning
confidence: 79%
“…By far radiofrequency energy has been extensively employed and studied for denervation procedures [3][4][5]7], although several technical aspects related to device catheters and power settings are under continuous evaluation. Laser energy was introduced in medicine several years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary artery denervation (PADN) is a surgical or interventional procedure aiming to modulate pulmonary artery (PA) pressure in patients with pulmonary arterial hypertension (PAH) of different etiologies [3][4][5][6]. The abatement of perivascular nerves within and around the pulmonary artery (PA) resulting in the decrease of sympathetic neural activity has been suggested as a pathophysiological consequence of PADN procedures [7]. Recently, PA stimulation mapping delineating the phrenic and laryngeal recurrent nerves close to the PA has been demonstrated to be feasible during transcatheter PADN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, A multi-center clinical trial proved that PADN can reduce PVR as well as increase 6-minute walk distance (6MWD) of PAH patients, and no adverse events related to surgery occurred, con rming the effectiveness and safety of PADN [13]. However, another clinical study found that the effect of PADN on some PAH patients is not obvious [14]. Moreover, the sample size of the current clinical research is too small.…”
Section: Introductionmentioning
confidence: 99%